Penerapan Arsitektur Tropis pada Pabrik Pengolahan Ikan Cakalang di Kecamatan Kabila Bone Desa Inengo - Fitri Rahman; Ernawati; Syafriyani (Transbahasa, 2025)
Indonesia, as the largest archipelagic country in the world, has enormous marine and fisheries potential, with around 3.25 million km2 of sea area and 2.55 million km2 of Exclusive Economic Zone. One of the leading sectors that supports the national economy is fisheries, with exports reaching IDR 73.68 trillion in 2019. Gorontalo Province, located in the northern part of Sulawesi Island, has enormous fisheries potential, especially skipjack tuna (Katsuwonus pelamis), which is a leading commodity with production that continues to increase from 2017 to 2021. However, skipjack tuna is sold in fresh form which is susceptible to damage, and there are limited processed products available on the market. To overcome this problem, it is necessary to develop efficient skipjack tuna processing based on modern technology. One solution that can be applied is processing with methods such as canning, drying, or smoking, which can extend the shelf life and increase the added value of the product. The development of skipjack tuna processing in Gorontalo can be supported by a Tropical Architecture approach, which is designed according to the tropical climate conditions in the area. This approach will not only create comfortable, efficient, and environmentally friendly buildings, but also support the sustainability of natural resources and increase the competitiveness of Gorontalo's fishery products in local and international markets.